Dielectric characterization of Ba0.6La0.4Sn0.6Mn0.4O3 ceramic - Primus, Walter Charles; Shaari, Abdul Halim; Wan Yusoff, Wan Mohamad Daud; Talib, Zainal Abidin (Malaysian Solid State Science and Technology Society, 2010)
The prepared Ba0.6La0.4Sn0.6Mn0.4O3 ceramic sample using solid state technique has been studied and its dielectric behaviour as a function of frequency and temperature are presented in normalized form. At -25 to 75 ºC, the dielectric spectra displayed the behaviour of low frequency dispersion (LFD) where some of the charge carriers (electronic) are bound and some are moving freely. However, at elevated temperature above 75 ºC, the carrier’s blockade occurred due to the rising up of interfacial and internal barrier effect at low and intermediate frequency, respectively.